Revisiting a central prediction of the Gill Oxygen Limitation Theory: Gill area index and growth performance. Issue 3 (27th February 2023) - Bigman, Jennifer S.; Wegner, Nicholas C.; Dulvy, Nicholas K.
Abstract: The Gill Oxygen Limitation Theory (GOLT) posits that a mismatch in oxygen supply and demand stemming from geometric constraints on gill surface area limits metabolic rate and energy available for biological processes. This theory has been suggested to explain numerous phenomena observed with warming yet is based upon a relationship among maximum size, growth, and gill surface area established over 40 years ago. However, the metric used in this relationship to characterize gill surface area, gill area index, fails to capture the known variability in the scaling of gill surface area and is biased by the sizes at which gills were measured. Here, we revisit a central prediction of the GOLT, asking four key questions that examine limitations in the original relationship. We find that gill area index does indeed explain variation in growth performance across 132 species of fish and this relationship is strikingly similar to the original relationship across 42 species. Yet, we argue that gill area index is not an adequate measure of gill surface area because (1) gill surface area has a non‐linear relationship with size and, thus, changes ontogenetically as an individual grows over time and (2) because it is based on mean estimates of both gill surface area and body mass. Indeed, we show that the value of gill area index for a given species is variable depending on how it is calculated. We therefore suggest a pathway forward for assessing whether gill surface area is an important factor in explaining variation in growth performance.